Stabilization of Coastal Embankments with Geotextile and Gabion Structures: Insights from a Tidal Zone Road Project - Dian Kharisma Dewi; Ferly Oktavia (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
This study presents a technical overview of a coastal road embankment constructed in a tidal zone of a small island in Indonesia. The objective is to document the integrated application of non-woven geotextile and multi-level gabions as a stabilization system on moderately strong subgrade soils affected by tidal dynamics. The research method involved descriptive analysis based on as-built documentation and field data, including California Bearing Ratio (CBR) tests at three locations. The results showed CBR values ranging from 41.11% to 60.84%, which classify the subgrade as moderately strong. Despite this, the use of geotextile was essential to prevent mixing of soft subgrade and fill material, provide load distribution, and ensure drainage, while the gabion structures acted as lateral confinement and toe protection against erosion caused by tidal infiltration. The findings suggest that soil strength alone is insufficient for coastal infrastructure design, and integrated stabilization measures should account for environmental forces such as saturation cycles and hydraulic pressure. This case offers a practical insight into adaptive geotechnical strategies for road construction in tidal zones, serving as a reference for similar projects in archipelagic and low-lying coastal regions.